Assessment of Spatial Variability of Soil Available Sulphur Using Geostatistical Techniques in a Part of Deccan Plateau of India - Rabi Narayan Sahoo (Journal of the Indian Society of Soil Science, 2022)
Soil heterogeneity, soil formation factors and other human induced activities cause spatial variation of soil available nutrients. Knowledge on spatial variability of soil nutrients is essential for their successful management in crop field. Soil available sulphur (S) is an important secondary nutrient and it may vary spatially at any scale. Hence, the present study was conducted to assess the spatial variability of soil available S using geostatistical techniques. About 132 georeferenced surface soil samples were collected form a cultivated area of Katol block of Nagpur district, Maharashtra, India. Soil available S was determined chemically and the descriptive statistical analysis of S showed its good variability in terms of per cent coefficient of variation (CV= 81.74%). The results of geostatistical analysis showed its spatial variability in terms of nugget: sill ratio (NS ratio). The NS ratio i.e., 0.37 indicated moderate spatial dependency of soil available S. The exponential model was found as a best suited semivariogram model for describing the spatial trend of soil S. Ordinary kriging (OK) technique was employed to generate spatial variability map of soil S to identify specific management zone of S. The present investigation suggested that the study area has moderate S content except north-east corner of the area, which is high in S content. Specific management of S is necessary to the central and north-west sides of the cropped areas of the study site. Thus, the study indicated a good potential of geostatistical technique especially with OK technique to generate S variability map for effective S management of the study area.